2021
DOI: 10.1149/1945-7111/ac099c
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Temperature Dependence of the Hydrogen Oxidation and Evolution Reaction Kinetics on Pt Electrocatalysts via PEMFC-based Hydrogen-Pump Measurements

Abstract: The hydrogen oxidation and evolution reaction (HOR/HER) has been widely investigated due to its importance for a broad variety of applications especially in electrolysis and fuel cells. However, owing to its extremely fast kinetics, kinetic data can only be obtained with experimental setups that provide very fast mass transport, so that the effect of hydrogen partial pressure (pH2) and kinetic limitations at high overpotentials are not yet fully understood. Here we report detailed kinetic investigations on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 62 publications
2
43
0
Order By: Relevance
“…Hydrogen evolution reaction (HER) is a simple model reaction that often features in the studies of electron-transfer kinetics in aqueous media. Hydrogen, obtained from electrolyzers, is a major contender considered for the storage of renewable energy. Generally, precious metals (Pt, Pd, or Ru) are used to catalyze the hydrogen evolution reaction in acidic media. Thus, HER is an extensively investigated electrochemical process of fundamental and technological importance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogen evolution reaction (HER) is a simple model reaction that often features in the studies of electron-transfer kinetics in aqueous media. Hydrogen, obtained from electrolyzers, is a major contender considered for the storage of renewable energy. Generally, precious metals (Pt, Pd, or Ru) are used to catalyze the hydrogen evolution reaction in acidic media. Thus, HER is an extensively investigated electrochemical process of fundamental and technological importance.…”
Section: Introductionmentioning
confidence: 99%
“…HER kinetics is investigated on the basis of Butler–Volmer analysis in the past. Tafel slopes, exchange current densities, and charge-transfer coefficients determined from Tafel plots and impedance spectra are used to characterize the HER activity of different catalysts. ,, , Apart from the conventional analyses, the HER is also investigated on the basis of Arrhenius theory. , The activation enthalpy at a particular overpotential helps compare the activity of different catalysts toward a reaction. Marković et al reported hydrogen evolution and oxidation reactions on Pt single-crystal surfaces in acidic and alkaline electrolytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HER and HOR involves the following equilibrium at the electrode surface, At Pt/C, this process can be divided into a series of elementary steps involving electrode surface sites, where an empty surface site (*) is required for hydrogen adsorption The kinetics of HER and HOR at an electrode surface at an applied overpotential can be described by the Butler–Volmer equation, where i is the resulting current density at an applied overpotential η; i 0 is the exchange current density of the process under the conditions employed; α a and α c are the charge transfer coefficients for the redox processes at the electrode surface; and F , , and T are the Faraday’s constant, gas constant, and temperature of the system, respectively. The exchange current of the system is expected to be dependent on the hydrogen and proton concentrations at the catalyst surface. , In the MEA, this corresponds to the hydrogen and proton content in the ionomer phase near the Pt/C particles, where the hydrogen content can be affected by gas partitioning. Assuming Henry’s law, the hydrogen concentration at the electrode surface should be proportional to the hydrogen partial pressure in the gas stream, p H 2 .…”
Section: Mea Modelmentioning
confidence: 99%
“…The different resistances associated with HER and HOR operation in an MEA can be analyzed using a proton-pump design, as depicted in Figure . , In this case, the resistances associated with the OER/ORR are replaced with the kinetically fast hydrogen equivalent, allowing only resistances associated with charge transport, hydrogen-related kinetics, and hydrogen or water-based mass transport processes to be more readily observed at both electrodes. This proton-pump design has been beneficial for investigating the kinetics associated with HOR and HER operation at Pt/C in PEM-based MEAs under standard and pressurized conditions, allowing accurate determinations of the exchange current and rate-limiting steps associated with the HOR/HER at Pt/C surfaces. Analyses of the mass transport resistance under hydrogen limiting currents in the proton-pump design have allowed a breakdown of the different contributions to the mass transport resistance in this current regime . Further, by placing one of the electrodes under inert conditions and the other under hydrogen flow, the ionic conduction pathway and corresponding ionic conductivity and active catalyst area of the catalyst layers can be determined using physical models. , While different resistances associated with HOR and HER operation have been determined using the proton-pump design independently, there has been little empirical work investigating each of the contributions to the cell impedance during operation.…”
Section: Introductionmentioning
confidence: 99%